PHYSICAL PARAMETERS OF HII/PDR COMPLEX IN ORION BAR ESTIMATED BY OBSERVATIONS OF 8 MM RECOMBINATION LINES. EFFECTIVE TEMPERATURE OF 1 С Ori STAR - Tsivilev, A. P.; Parfenov, S. Yu.; Sobolev, A. M. (Одеські астрономічні публікації, 2014)
Physical parameters of HII/PDR complex in Ori Bar were estimated using observations of recombination radio lines (RRL) of carbon (C), hydrogen (H) and helium (He) with RT-22 radio telescope in Pushchino. Possible structure of the complex is discussed. Effective temperature (Teff) of the star ionizing Orion nebula was estimated. Obtained estimate provides additional constraint to existing “spectral class – Teff“ calibrations for O-stars indicating that the q1 С Ori star with ≈ O6.5 V spectral class has Teff in the range 36 000–37 500 K